2015
DOI: 10.3389/fevo.2015.00114
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for additive effects of virus infection and water availability on phytohormone induction in a staple crop

Abstract: Infection with phytoviruses influences plant responses to environmental stress, but the biochemical mechanisms underlying these interactions are unknown. Infection of wheat (Triticum aestivum) with a cereal virus (Barley yellow dwarf virus, BYDV) has context-dependent effects on plant productivity and survival conditional to water stress, and we hypothesized this was due to phytohormone induction resulting from virus infection. We tested whether BYDV infection and water availability interact to influence hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Lastly, the separation differences between all compounds were optimized in MRM, achieving a detection limit of 5 nmol with excellent chromatographic peak shape and signal to noise ratio. Similar protocols have been used to quantify plant hormones, and these studies report hormone concentrations comparable to those reported here (Bastías et al., ,; Davis, Bosque‐Pérez, Popova, & Eigenbrode, ; Eberl, Hammerbacher, Gershenzon, & Unsicker, ; Ohnmeiss & Baldwin, ; Paulmann et al., ).…”
Section: Methodssupporting
confidence: 80%
“…Lastly, the separation differences between all compounds were optimized in MRM, achieving a detection limit of 5 nmol with excellent chromatographic peak shape and signal to noise ratio. Similar protocols have been used to quantify plant hormones, and these studies report hormone concentrations comparable to those reported here (Bastías et al., ,; Davis, Bosque‐Pérez, Popova, & Eigenbrode, ; Eberl, Hammerbacher, Gershenzon, & Unsicker, ; Ohnmeiss & Baldwin, ; Paulmann et al., ).…”
Section: Methodssupporting
confidence: 80%
“…Both infected barley cultivars showed an increase in SA concentrations compared to healthy plants, whereas the heat stimulus did not induce a response ( Figure 5B ). Davis et al (2015) showed a similar increase in SA for BYDV infected wheat plants. SA promotes ROS production, on the one hand, and ROS scavenging, on the other, in a temporally dynamic way ( Herrera-Vasquez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 53%
“…For example, changes in proteins involved in JA synthesis and accumulation were noted in a diversity of plants exposed to water deficit (Fan et al, 2009;Harb et al, 2010;Bonhomme et al, 2012;Ahmad et al, 2016;Haider et al, 2017), while other studies have indicated lack of JA induction in drought-stressed plants (Muñoz-Espinoza et al, 2015;Nachappa et al, 2016). The exact nature of interactions among the defensive responses of plants to biotic and abiotic stresses remains understudied, however, despite their importance to plant-pathogen, plant-insect, and plant-pathogenvector interactions (Asselbergh et al, 2008;Erb et al, 2011;Davis et al, 2015b;Nachappa et al, 2016).…”
Section: Overview Of General Molecular Responses Of Plants To Biotic mentioning
confidence: 99%